A Theory of Fads, Fashion, Custom, and Cultural Change as Informational Cascades - Bikhchandani, Sushil; Hirshleifer, David; Welch, Ivo (Journal of Political Economy, 1992)
An informational cascade occurs when it is optimal for an individual, having observed the actions of those ahead of him, to follow the behavior of the preceding individual without regard to his own information. We argue that localized conformity of behavior and the fragility of mass behaviors can be explained by informational cascades.